A Study on Challenges to Health Care Delivery Faced by Cancer Patients in India During the COVID-19 Pandemic - Mitra, Manasij (J Prim Care Community Health, 2020)
INTRODUCTION: Access to health care and care delivery during the COVID-19 pandemic may be challenging for cancer patients. Several guidelines have been developed, which recommend treatment adjustments depending on the site of cancer, grade, and stage. However, few studies in India and across the globe have looked into the real challenges faced by cancer patients and assessed the effectiveness of the adopted interventions. This study was undertaken with the objective to study the challenges faced by cancer patients in India during the COVID-19 pandemic. MATERIALS AND METHODS: This was a cross-sectional study undertaken between May 1, 2020 and May 15, 2020. A link to a prestructured questionnaire was sent through email to 100 randomly selected cancer patients in different stages of treatment and follow-up. Data were decoded and entered in Microsoft Excel 2010 and analyzed using descriptive statistics. RESULTS: Slot availability for teleconsultation, network issues, deferral of radiotherapy dates and long waiting hours beyond appointment time, transportation problems from residence to hospital, restriction of visitors/attendants, deferral of surgery, deferral of tumor boards, delay and deferral of advice of the nutritionist, problems faced in extension of visa, unavailability of peer group support services and psychological counseling sessions, difficulty in maintaining precautionary measures, availability of chemotherapy medications and availability of chemotherapy slots in day care were cited as problems faced by cancer patients. Majority (91.7%) of the study respondents mentioned an increase in their anxiety levels. CONCLUSION: As highlighted in the study, cancer patients faced challenges in cancer care delivery during the COVID-19 pandemic. This study suggests the need for larger studies on cancer patient care during a pandemic.